2009
DOI: 10.1055/s-0031-1278352
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of soluble receptor for advanced glycation end products in non-ST elevation myocardial infarction patients

Abstract: A dvanced glycation end products (AGEs) are a heterogeneous group of irreversible adducts resulting from nonenzymatic glycation and oxidation of proteins, lipids and nucleic acids (1,2). AGEs act on cell receptors for AGEs (RAGEs). There are three forms of RAGEs (2-5) -full-length, N-truncated and C-truncated soluble RAGEs (sRAGE). The interaction of full-length RAGE with AGEs leads to increased expression of adhesion molecules, including soluble vascular cell adhesion molecule-1 (sVCAM-1) and the cytokine tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 42 publications
1
32
0
1
Order By: Relevance
“…It has been reported that the concentration of sRAGE in the plasma of patients with coronary artery disease is lower than in control subjects [167]. Similar findings have been reported by McNair et al [168] in patients with non-ST-segment elevation myocardial infarction (NSTEMI). McNair et al also reported that lower serum levels of sRAGE were associated with higher levels of AGEs, AGEs/sRAGE, sVCAM-1, and TNF-α.…”
Section: Age Rag and Srage And Coronary Artery Diseasesupporting
confidence: 76%
“…It has been reported that the concentration of sRAGE in the plasma of patients with coronary artery disease is lower than in control subjects [167]. Similar findings have been reported by McNair et al [168] in patients with non-ST-segment elevation myocardial infarction (NSTEMI). McNair et al also reported that lower serum levels of sRAGE were associated with higher levels of AGEs, AGEs/sRAGE, sVCAM-1, and TNF-α.…”
Section: Age Rag and Srage And Coronary Artery Diseasesupporting
confidence: 76%
“…Author's laboratory has reported that serum levels of sRAGE were low in patients with non-ST elevation myocardial infarction. 182 Also, it has been reported that low levels of serum sRAGE is predictor for restenosis following percutaneous coronary intervention. 183 These data suggest that AGE-RAGE axis is involved in the pathogenesis of atherosclerosis.…”
Section: Receptor-mediated Mechanismmentioning
confidence: 99%
“…32,33 Our group has previously shown that the levels of serum sRAGE are lower, while the serum levels of AGE, sVCAM-1, and TNF-α are higher in subjects with NSTEMI as compared with healthy controls. 34 Studies demonstrating the mechanism underlying the relationship between serum sRAGE levels and cholesterol levels are lacking. Blockade of RAGE by using sRAGE abolishes vascular complications of diabetes in animal models.…”
Section: Discussionmentioning
confidence: 99%